In vivo antiplasmodial potential of aqueous seed extract of Ricinus communis - Peace ME. Ubulom; Ette O Ettebong; Edidiong J. Udofia; Rachel S Inyang Etuk (Shahrekord University of Medical Sciences, 2019)
Introduction: Ricinus communis is used by the people of Niger-Delta region of Nigeria, for the treatment of various ailments, especially malaria. This study evaluated the antiplasmodial potentials of the aqueous seed extract of R. communis, using Plasmodium berghei berghei. Methods: Acute toxicity study was carried out to determine the median lethal dose (LD50) of the extract. Antiplasmodial effect of the extract was assessed in suppressive, repository/ prophylactic and curative models, using Swiss albino mice (15-29 g). Mice were infected intraperitoneally with 0.2 mL of parasitized blood. Extract doses administered were 54.77, 109.54 and 164.32 mg/kg/d of the seed extract and each dose had 6 replicates. Artesunate (5 mg/kg/d) and pyrimethamine (1.2 mg/kg/d) were used as standard drugs, while distilled water (10 mL/kg/d) served as control. Results: Acute toxicity study produced LD50 of 547.72 mg/kg. The extract demonstrated a dosedependent reduction in parasitaemia in all tests. At the end of 4-day test, suppressive effect of 20.80, 49.00, 75.00 and 88.40% were obtained for doses 54.77, 109.54 and 164.32 mg/kg/d of the seed extract and artesunate, respectively. In the repository test pyrimethamine was more potent (72.26%) than the seed extract (9.47%-51.42%). The extract also exhibited appreciable curative effect. The activity of the seed extract was significant when compared with the control (P < 0.05). Mice treated with the seed extract and drugs survived for longer duration than the control group. Conclusion: The aqueous seed extract of R. communis has antiplasmodial potential and its active principle should be elucidated and further investigated to help in the ongoing fight against malaria.